Comparison of Trihalomethane Formation Using Chlorine-Based Disinfectants Within a Model System; Applications Within Point-of-Use Drinking Water Treatment - Clayton, Gillian E.; Thorn, Robin M. S.; Reynolds, Darren M. (Frontiers in Environmental Science, 2019)
Point-of-use (POU) drinking water treatment systems provide solutions for communities where centralised facilities are unavailable. Effective POU systems treat and reduce the number of pathogens in POU water supplies often employing disinfection. Chlorine disinfection results in the formation of disinfection by-products (DBPs), such as trihalomethanes (THMs), through the reaction of chlorine with natural organic matter (NOM) over time. Although THMs are known to be harmful to human health, little is known about their production within POU systems. This study compares the disinfectants; Electrochemically Activated Solutions (ECAS), hypochlorous acid (HOCl) and sodium hypochlorite (NaOCl), with respect to their potential to produce THMs within POU drinking water systems. Headspace solid-phase microextraction (HS-SPME) gas chromatography mass spectrometry (GC-MS) was utilised to quantify THMs in treated water samples containing NOM (Suwannee River humic acid, 4 mg L-1). All disinfection treatments were matched to free chlorine concentrations of 1, 3 and 5 mg L-1, using reaction times of 1, 5 and 10 minutes. THMs were produced at free chlorine concentrations of 5 mg L-1 and at reaction times of 5 and 10 minutes for all disinfectants. ECAS or HOCl, resulted in the formation of significantly lower total THM concentrations across all reaction times and free chlorine concentrations, compared to NaOCl. ECAS can be generated at the POU requiring only water, salt and energy for production, and this study demonstrates that its use results in reduced formation of THMs, compared with NaOCl. Further work is required to replicate these findings within scaled-up POU water treatment systems.